The Effects of Vitamin D Supplementation on Athletic Performance and Injury Prevention - Amani Abushamma (Bowling Green State University, 2022)
Vitamin D supplementation has numerous effects on athletic performance and plays a significant role in preventing an athlete's risk of getting injuries. Vitamin D has an impact on numerous physiological functions such as: bone health, muscle function, inflammatory response, and immune function. An athlete's bone and muscle health are essential for maximum performance and career success. A bone fracture due to vitamin D deficiency can delay an athlete's training and ultimately inhibit obtaining a collegiate scholarship and/or contract. A cross sectional study found that more than half of athletic trainers did not view 25-hydroxyvitamin D(25[OH]) testing and vitamin D supplementation as a necessary use of athletic program funds. There is disagreement over vitamin D in the applied and clinical setting. Further studies are needed in which a host of variables are investigated regarding the optimal dosages of vitamin D supplements for athletes. The objective of this review is to investigate current research looking at the effects of vitamin D supplementation on athletic performance and injury prevention as well as optimal doses of vitamin D3 for athletes. Adequate vitamin D supplementation can be utilized to prevent and reduce the risk of frequent injuries among athletes.